2014
DOI: 10.1016/j.fitote.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial tetraoxygenated xanthones from the immature fruits of Garcinia cowa

Abstract: A phytochemical investigation of the acetone extract from the immature fruits of Garcinia cowa led to the isolation of two novel tetraoxygenated xanthones, garcicowanones A (1) and B (2), together with eight known tetraoxygeanted xanthones. Their structures were determined by spectroscopic analysis. All isolated compounds were evaluated for their antibacterial activity against Bacillus cereus TISTR 688, Bacillus subtilis TISTR 008, Micrococcus luteus TISTR 884, Staphylococcus aureus TISTR 1466, Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 18 publications
(26 reference statements)
1
28
0
Order By: Relevance
“…All of these four compounds exhibited moderate activity against Plasmodium falciparum with their IC 50 values in the range of 1.50-3.00 µg/mL [2]. Evaluation of the antibacterial activity against Gram-positive bacteria: B. cereus TISTR 688, B. subtilis TISTR 008 and M. luteus TISTR 884 of compound rubraxanthone (5) and cowanin (6) showed that they both exhibited good activity with MICs of 6 in the range of 4-8 μg/mL while 5, had better activity with MICs in the range of 1-2 μg/mL [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these four compounds exhibited moderate activity against Plasmodium falciparum with their IC 50 values in the range of 1.50-3.00 µg/mL [2]. Evaluation of the antibacterial activity against Gram-positive bacteria: B. cereus TISTR 688, B. subtilis TISTR 008 and M. luteus TISTR 884 of compound rubraxanthone (5) and cowanin (6) showed that they both exhibited good activity with MICs of 6 in the range of 4-8 μg/mL while 5, had better activity with MICs in the range of 1-2 μg/mL [11].…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical studies and pharmacological activities of G. cowa from Thailand were reported recently [2 -6]. According to previous reports, main chemical constituents of G. cowa are xanthones which were demonstrated interesting bioactivities such as antimalarial [2], antimicrobial [3,5,7], anti-inflammatory [4,8], antioxidant [3,4,9], antibacterial [5,10,11], antitumor-promoting activity [12] and cytotoxic activities [13 -15].…”
Section: Introductionmentioning
confidence: 99%
“…Branches no [78] Dihydroxyprenyl xanthone acetylated Oenothera biennis Roots no [79] Doitunggarcinone C Garcinia propinqua Twigs no [80] Dulcisxanthone H Garcinia dulcis Branches no [81] Dulcisxanthone I Garcinia dulcis Branches no [81] Dulcisxanthone J Garcinia dulcis Stem barks no [82] Dulcisxanthone K Garcinia dulcis Stem barks no [82] Dulcisxanthone L Garcinia dulcis Stem barks no [82] Epiisobractatin Garcinia bracteata Leaves yes [38] Esculentin A Garcinia esculenta Twigs no [83] Fuscaxanthone I Garcinia fusca Roots yes [84] Fuscaxanthone J Garcinia fusca Roots no [85] Fuscaxanthone K Garcinia fusca Roots no [85] Garcibractatin A Garcinia bracteata Leaves yes [86] Garcibracteatone Garcinia bracteata Leaves yes [38] Garcibractone A Garcinia bracteata Leaves yes [86] Garcibractone B Garcinia bracteata Leaves yes [86] Garcicowanone A Garcinia cowa Fruits no [87] Garcicowanone B Garcinia cowa Fruits no [87] Garciesculenxanthone A Garcinia esculenta Twigs yes [88] Garcihombronone A Garcinia hombroniana Twigs no…”
Section: Garcinia Schomburgkianamentioning
confidence: 99%
“…This genus is well known as a rich source of xanthones, 1-10 caged xanthones, [11][12][13][14][15][16][17][18][19][20][21] flavonoids, 22 terpenoids, 23 biphenyls, [24][25] and benzophenones. [26][27][28][29][30] Many of these compounds have a wide range of biological and pharmacological activities, including antimicrobial, 29,31 antidepressant, 29 anti-HIV, 29,32 antibacterial, 2,3,9,10,18,22 and cytotoxic activities. 6,8,[12][13][14][15][16][17]27,29 In a previous paper we reported the isolation of xanthones, caged…”
mentioning
confidence: 99%
“…xanthones, and rearranged benzophenones from the twig and root extracts of Garcinia propinqua collected from Doi Tung, Chiang Rai Province, Thailand. 2,33 Herein, the isolation and identification of seven new caged xanthones, doitunggarcinones E-K (1-7), as scalemic mixtures, together with 10 known compounds (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) from the stem bark extract of G.…”
mentioning
confidence: 99%